The influence of perceived quality and viral marketing on the decision to purchase Momoyo Ice Cream according to the Islamic business perspective - Nurhayati, Nurhayati; Fadillah, M.Rizky; Selvina, Mia; Nuraziza, Sania (Indonesia Auditing Research Journal, 2024)
This research aims to analyze the influence of perceived quality and viral marketing on purchasing decisions for Momoyo ice cream. The main problem in this research is that Momoyo is still unable to compete with other ice cream brands, especially brands that have previously been established in the market. The ice cream industry has experienced rapid development in the last few decades. The demand for ice cream continues to increase, especially in summer and in areas with hot climates. Consumers are not only looking for ice cream as a refreshing snack, but also as a product that provides experience and joy. This research uses an exploratory research method with a quantitative approach using the Lemeshow formula approach, with a fixed sample of 97 respondentswhich was distributed via Google Form which was tested using IBM SPSS Statistics 26.The research results show that the perceived quality variable (X1) has a positive and significant effect on purchasing decisions (Y). Meanwhile, for the second hypothesis (X2), viral marketing does not have a positive and significant effect on purchasing decisions (Y). In conclusion, perceived quality and viral marketing simultaneously influence purchasing decisions.